Red Hat trick. (Economist, 1998)
Reports the September 29, 1998, decision of Intel and Netscape to acquire, along with two venture-capital firms, a minority stake in Red Hat Software. Undisclosed amount of their investment in Red Hat; Red Hat's distribution of Linux, the computer operating system developed by volunteer programmers around the world; Estimate of the number of Linux users; How the deal will help Red Hat and Linux expand their reach.